2018
DOI: 10.1016/j.jcot.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Intrathoracic fracture—Dislocation of the shoulder

Abstract: Intrathoracic dislocation of the shoulder is a rare condition that usually occurs after high-energy trauma. Etiology, mechanism of injury and associated lesions are diverse. We present the case of a patient who suffered a great height fall, treated with removal of the humeral head and implantation of a shoulder hemiarthroplasty. One year after the surgery, the patient was pain free and the Constant score was 70 points.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Therefore, there is no precise consensus on the appropriate actions and timing to achieve better treatment outcomes and reduce the risk of complications. Injuries of this nature are usually caused by high-energy trauma, such as motor vehicle accidents, falls from stairs, or falls from heights [2][3][4][5][6]. In these and similar cases, the impact not only fractures the proximal part of the humerus but also forces the humeral head through all the tissues and ribs into the chest cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is no precise consensus on the appropriate actions and timing to achieve better treatment outcomes and reduce the risk of complications. Injuries of this nature are usually caused by high-energy trauma, such as motor vehicle accidents, falls from stairs, or falls from heights [2][3][4][5][6]. In these and similar cases, the impact not only fractures the proximal part of the humerus but also forces the humeral head through all the tissues and ribs into the chest cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars have suggested that it is necessary to remove fragments only when there are cardiopulmonary complications. The reason for removal of bone fragments from the humeral head is that there may be related complications, such as infection or foreign body reactions [18]. It has been reported that the retained humeral head was removed 6 weeks late, and was embedded in the pulmonary parenchyma with extensive adhesion, requiring extensive resection [35].…”
Section: Discussionmentioning
confidence: 99%
“…Intrathoracic fracture-humeral head dislocation has been rarely reported and requires a combination of high-energy trauma and speci c mechanisms. Enumerating the mechanism of injury, most of which are high-energy injuries.We can review including 18 falls from heigh [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], 7 motor vehicle accidents [19][20][21][22][23][24][25], and 2 were knocked down by motor vehicles [26,27], 2 cases of falling from standing height [28,29], and 1 case of falling from a bicycle [30].…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have suggested that it is necessary to remove fragments only when there are cardiopulmonary complications. The reason for the removal of bone fragments from the humeral head is that there may be related to complications, such as infection or foreign body reactions (18). It has been reported that the retained humeral head was removed six weeks later and was embedded in the pulmonary parenchyma with extensive adhesion requiring extensive resection (29).…”
Section: Discussionmentioning
confidence: 99%
“…This study investigates a case report of intrathoracic fracture-dislocation of the humeral head. The reviews included falls from height (n=18) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), motor vehicle accidents (n=7) (19)(20)(21)(22)(23)(24)(25), knockdown by motor vehicles (n=2) (26,27), falling from standing height (n=2) (28,29), and falling from a bicycle (n=1) (30).…”
Section: Introductionmentioning
confidence: 99%